2013
DOI: 10.1007/s00464-013-3164-4
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection training with ex vivo human gastric remnants

Abstract: ESD requires the endoscopist to perform a surgical dissection. Until now, development of these skills required intensive training on porcine models that are not widely available. We were able to create a method using the excised portion from sleeve gastrectomy patients, providing a more accessible and cost-effective model for ESD training and potentially other endoscopic therapeutic modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
1
5
1
Order By: Relevance
“…The adjusted mean dissection speed found in our study (22.1 mm 2 /minute) was very close to that reported by Jacques et al. (23.3 mm 2 /minute) in a similar porcine model 14 . We believe that, with experience, the junior endoscopist not only progresses in organising different strategies to resect ‘lesions’ of different sizes and locations, but also very practically in the use of ESD‐associated devices.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The adjusted mean dissection speed found in our study (22.1 mm 2 /minute) was very close to that reported by Jacques et al. (23.3 mm 2 /minute) in a similar porcine model 14 . We believe that, with experience, the junior endoscopist not only progresses in organising different strategies to resect ‘lesions’ of different sizes and locations, but also very practically in the use of ESD‐associated devices.…”
Section: Discussionsupporting
confidence: 89%
“…This might be due to a lack of attention during the procedure or, more likely, to an excess of confidence of the endoscopist. The complication rate reported in our study was much lower than that found in other pig models 14 . This might reflect the fact that ‘junior’ endoscopists were carefully selected for ESD training and had mostly already performed endoscopic retrograde cholangiopancreatography or other interventional techniques.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Moreover, Fukui et al[30] have found that complete gastrectomy does not improve survival outcomes compared with ESD, and complete gastrectomy may even adversely affect the long-term outcomes of patients with early RGC. However, performing ESD in the remnant stomach is challenging due to the narrow workspace and the presence of severe fibrosis, adhesions and staples under the suture lines[31,32]. We reviewed all published English language literature to assess the efficacy and feasibility of ESD in treating early RGC.…”
Section: Endoscopic Submucosal Dissection For Gastric Stump Cancermentioning
confidence: 99%